Content analysis of message strategy in ERHA X AQUA Co-Branding through social media instagram (Jurnal Kajian Media, 2021)
ERHA is an Indonesian-based beauty brand founded in 1999, ERHA co-branded with AQUA, which is known as the top of mind in its category, and launched a series of hydrating skincare products that represent the characteristics of the two brands. ERHA and AQUA use social media Instagram as a place to carry out marketing communications to their audience. The right message strategy is needed so that the marketing communication objectives of the ERHA and AQUA co-branding can be conveyed properly to the target audience. This study aims to identify and describe the marketing communication message strategy used by ERHA and AQUA on Instagram. This study uses the concepts of co-branding which consists of familiarity, product fit, reputation, attitude toward co-branding, and trust, and also the message strategy concepts which consists of cognitive message strategy, affective message strategy, and conative message strategy. This research is descriptive quantitative with a content analysis method. The population in this study is all post feeds related to co-branding ERHA and AQUA on Instagram ERHA and AQUA in the period February 2021 – December 2021, which is a total of 36 posts. Keywords: Co-branding, Message Strategy, Social Media, Instagram.